'Digital Humanities and Artificial Intelligence in Women's History: The VOICES project (Ireland)' - Mc Kenna, Lucy; McShane, Bronagh; Ohlmeyer, Jane; O'Sullivan, Declan; Patterson, Daniel (My University, 2026)
The first part of the chapter offers a brief introduction to the ‘digital windfall’ of Irish historical data (Part I) while part two discusses the innovative technologies and methods that the VOICES project will harness, including a Knowledge Graph and AI informed approaches. Two detailed case studies, that reflect ‘work in progress’ on records from the Irish Court of Chancery (Part III) and testamentary records (Part IV) are explored in the second half of the chapter. We reflect on the possibilities that machine learning affords historians and the processes we have been developing to avail of these opportunities. We argue that the transparent and ethical use of innovative technologies, grounded in the Semantic Web, Linked Open Data, and AI, can enable a new paradigm of historical research, which allows us to recover in a holistic and integrated way the marginalised voices and lived experiences of women in early modern Ireland.
PUBLISHED
https://doi.org/10.1093/9780197852675.003.0009
Keywords: Ireland; women; gender; 1641 Depositions; wills; Court of Chancery; early modern; digital humanities; Knowledge Graph; Linked Data; Artificial Intelligence; Digital Humanities; Digital Humanities; 1641 Depositions; Digital Humanities; Early Modern Ireland; IRELAND; Knowledge Graphs; Linked Open Data; WOMEN; Wills; History